Fredholm boundary-value problem for the two-term sequential fractional differential equation - Boichuk, O.; Feruk, V. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9 We establish necessary and sufficient conditions for the solvability and the general form of the solution to the linear boundary-value problem for the two-term sequential differential equation. The following two cases are considered: 1) the sequential derivative is a combination of two fractional Caputo derivatives; 2) the sequential derivative is a combination of the ordinary derivative and the Caputo fractional derivative.